Analisis Social Return on Investment (SROI) Program CSR Pemanfaatan Limbah Fly Ash dan Bottom Ash (FABA) PT PLN Nusantara Power UP Pacitan - Dasra Viana, Eka; Ratna Dewi, Farida; Mutasowifin, Ali; Tri Listirta, Risky; Afrida Pebriana, Lila (Jurnal Manajemen dan Organisasi, 2024)
This research presents an evaluation of the implementation of the Corporate Social Responsibility programme based on the use of Fly Ash and Bottom Ash (FABA) waste. The form of programme implementation is the use of coal combustion waste to make products such as bricks and paving blocks. The products are used in the construction of livable houses, village road casting and soil stabilisation in several areas of Pacitan Regency, East Java. This research uses a qualitative descriptive approach by examining the social and economic impacts on local communities through six stages of Social Return on Investment (SROI) analysis. The measured social benefits were greater than the investment with a ratio of 2.4:1. This means that for every IDR 1 invested, IDR 2.4 benefits were realised. This shows that the programme has the potential for economic, social and environmental sustainability.